Pengembangan E-Jobsheet Pembuatan Pola Kamisol Pada Mata Pelajaran Costume Made di SMK Negeri 1 Jabon - Maratus Sholichah; Deny Arifiana (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
This research aims: (1) to describe the feasibility of e-jobsheets for making camisole patterns in costume made subjects at State Vocational Schools 1 Jabon, (2) to describe student learning outcomes regarding the development of e-jobsheets for making camisole patterns for costume made subjects at State Vocational Schools 1 Jabon. This research uses the research and development (RnD) research method. The results of this research state that (1) the level of feasibility of developing an e-jobsheet for making camisole patterns by media experts and material experts with an average score of 4.23 in the very feasible category, (2) student learning outcomes for developing an e-jobsheet for making camisole patterns The costume made subject obtained a percentage of 95% which was declared passed and 5% which was declared not passed.